Does market integration promote green technology innovation? Evidence from China - Lin, Tao; Chen, Zhao (Frontiers in Environmental Science, 2022)
Understanding how to improve green technology innovation is critical to addressing environmental pollution and climate change. Using data from the annual reports of Chinese listed manufacturing firms from 2002 to 2018, this paper investigates the impact of market integration on firms’ green technology innovation. The research design relies on the instrumental variable approach. The results show that both commodity market integration and factor market integration can significantly promote green technology innovation. However, heterogeneity exists across regions, ownership systems, and industry types. Exploring the mechanisms, we find that commodity market integration affects firms’ green technology innovation mainly by expanding market size, intensifying market competition, and promoting technology spillovers. Factor market integration influences firm green technology innovation by optimizing resource allocation and reducing government intervention.